The influence of the disordered dipole subsystem on the thermal conductivity of the CO solid at low temperatures - Sumarokov, V.; Jeżowski, A.; Stachowiak, P. (Физика низких температур, 2009)
The thermal conductivity of solid CO was investigated in the temperature range 1–20 K. The experimental temperature dependence of thermal conductivity of solid CO was described using the time-relaxation method within the Debye model. The comparison of the experimental temperature dependences of the thermal conductivity of N₂ and CO shows that in the case of CO there is an additional large phonon scattering at temperatures near the maximum. The analysis of the experimental data indicates that this scattering is caused by the frozen disordered dipole subsystem similar to a dipole glass. The scattering is described by the resonant phonon scattering on tunnelling states and on low-energy quasi-harmonic oscillations within the soft potential model.